2016
DOI: 10.1016/j.addbeh.2016.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative contextual risk at birth in relation to adolescent substance use, conduct problems, and risky sex: General and specific predictive associations in a Finnish birth cohort

Abstract: Background Research indicates that risk factors cluster in the most vulnerable youth, increasing their susceptibility for adverse developmental outcomes. However, most studies of cumulative risk are cross-sectional or short-term longitudinal, and have been based on data from the United States or the United Kingdom. Using data from the Northern Finland Birth Cohort 1986 Study (NFBC1986), we examined cumulative contextual risk (CCR) at birth as a predictor of adolescent substance use and co-occurring conduct pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…Prior research (Hawkins, Catalano, & Miller, 1992), including prior analyses with this sample (January et al, 2016; Mason et al, 2016) have demonstrated a link between cumulative risk exposure and later alcohol involvement. This link could be due to either genetic (e.g., family history of alcohol abuse) or environmental (e.g., parental modeling) influences, or a combination of both.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Prior research (Hawkins, Catalano, & Miller, 1992), including prior analyses with this sample (January et al, 2016; Mason et al, 2016) have demonstrated a link between cumulative risk exposure and later alcohol involvement. This link could be due to either genetic (e.g., family history of alcohol abuse) or environmental (e.g., parental modeling) influences, or a combination of both.…”
Section: Discussionmentioning
confidence: 78%
“…Prior research also has documented positive associations between cumulative contextual risk and adolescent alcohol use. For example, in an analysis of data from the NFBC1986, cumulative contextual risk in early childhood was a positive predictor of alcohol and other substance use in mid-adolescence (Mason et al, 2016; January et. al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescence is another critical developmental period wherein successful completion of school is essential for the transition to adulthood and either postsecondary education/training or entry into the workforce. One recent study from the current project found that exposure to multiple contextual risks at birth increased the likelihood of substance use and co-occurring difficulties (e.g., conduct problems) in adolescence (Mason et al 2016). Although this study provided initial support for the long-term impact of multiple contextual birth risks, it did not consider the school context; therefore, it remains unknown how cumulative risk exposure at birth impacts long-term functioning in school.…”
Section: Introductionmentioning
confidence: 88%
“…Given our interest in linking childhood cumulative risk to adolescent outcomes, the analysis sample is limited to members of the birth cohort who participated in the adolescent self-report survey and who have valid data on the majority of our cumulative risk indicators, which are discussed below ( n = 5,743). Prior analyses using these data have tested for selective attrition, finding that the analysis sample has slightly more females, fewer low birth weight babies, and fewer children of mothers who smoked during pregnancy than the original live-born birth cohort (Mason et al, 2016). The ethical committee of the Northern Ostrobothnia Hospital District approved the study.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of studies, Sameroff and colleagues (1987a; 1987b; 1993) have reported evidence that increases in the number of childhood risk factors predict a wide range of maladaptive outcomes among children and adolescents. Additional studies have linked cumulative risk exposure to internalizing problems, externalizing problems, juvenile delinquency, and drug use (Adelmann, 2005; Dekovic, 1999; Farrell, Danish, and Howard, 1992; Gerard and Buhler, 2004a; Gerard and Buhler, 2004b; Jessor et al, 1995; Mason et al, 2016; Morales and Guerra, 2006; Stouthamer-Loeber et al, 2002), as well as reduced academic performance, educational attainment, and cognitive functioning (Dubow and Luster, 1990; Gassman-Pines and Yoshikawa, 2006; January et al, 2017; Luster and McAdoo, 1994). …”
Section: Cumulative Risk Perspectivementioning
confidence: 99%